STUDY ON PRIMING METHODS TO ENHANCE THE VIABILITY AND VIGOR OF TREMA (Trema orientalis LINN. BLUME) SEEDS - Yuniarti, Naning; Kurniaty, Rina; Syamsuwida, Dida (Association of Indonesian Forestry and Environment Researchers and Technicians, 2019)
Trema is one of tropical forest trees that has many advantages such as wood for building, pulp and charcoal, leaves for medicine and bark for dye material. The constrain of the development of this species is the difficulties of the seeds to germinate and the rapid deterioration of the seeds after being stored. Therefore, there should be a right method to solve the problems. The aim of the study is to determine the proper method of priming to enhance the viability and vigor of trema seeds after storage. Randomized Complete Design was employed in this trial by priming the seeds before and after storage. The treatments werepriming methods including: control (no priming), matriconditioning with ash, osmoconditioning by soaking of 5% H2O2, humidify with water and hydrated-dehydrated process. The observed parameters were thepercentages and speed of germination. The results showed that the treatment method of priming the best for this type of Trema, both before storage and after storage hydration is the treatment of dehydration. Before storage, can increase the value of germination percentage and speed of germination respectively 15% and 0.9% /Etmal. After the storage, treatment hydration dehydration can increase 17% germination and speed of germination of 1.25% / Etmal.